Passive aerated in-vessel composting of food waste with the addition of Sabah ragi for campus sustainability: mass balance, dwarf crape jasmine growth and techno-economic study - Mohd Al, Mussa Ugak; · Nurul Elyani, Mohamad; Mariani, Rajin; Junidah, Lamaming; Sariah, Saalah; Abu Zahrim, Yaser (Springer, 2023)
Composting is a sustainable solution on campus for waste management as it is essential for achieving the ideal circular economy. This study aims to evaluate the mass balance during the composting process, the efect of the compost on plant growth, and the techno-economic feasibility of the composting system for food waste management on campus. The mass balance was evaluated based on the initial and fnal masses of the composting process. The plant growth of dwarf jasmine and phytotoxicity using the compost produced, as well as the techno-economics of the compost system, were evaluated. In terms of mass balance, the mass reduction was mainly due to water evaporation, leachate, excess moisture and dry matter loss, and gas emissions. The total mass reduction and compost produced were ~67% and~27% of the initial mass, respectively. Based on the techno-economic analysis, the passive aeration in-vessel composting system will be economically feasible on the UMS (KK campus) and could potentially generate a proft of MYR 32,723.75 (USD 7343.75) per year.